Allyl trenbolone to control estrus in gilts-effect of dose - Duane L Davis; J M Robl; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1979)
Replacement gilts frequently do not fit smoothly into existing breeding and farrowing schedules because time of estrus cannot be predicted. Being able to program replacement gilts into a breeding herd would improve management, so we investigated the effectiveness of a synthetic progestogen, allyl trenbolone , to control estrus in gilts. Allyl trenbolone is not presently available to swine producers.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Allyl trenbolone; Estrus; Gilts